Testosterone therapy for hypoactive sexual desire disorder in women - Misiuk, Jagoda Misiuk; Kopeć, Karolina; Bartoszek, Aleksandra; Adamiuk, Julia; Marut, Agnieszka; Biskup, Marta; Skuba, Adriana; Załuska, Katarzyna; Nykiel, Sylwia; Świdniak, Agnieszka (Quality in Sport, 2025)
Introduction and Purpose: Testosterone plays a pivotal role in women’s sexual health, influencing sexual desire, arousal, and satisfaction. This hormone, primarily produced in the ovaries, adrenal glands, and adipose tissue, declines with age, especially during menopause, leading to sexual dysfunction such as hypoactive sexual desire disorder (HSDD). The purpose of this article is to review the role of testosterone in female sexual function, evaluate the efficacy and safety of testosterone therapy (TRT) for women with HSDD, and discuss the ongoing challenges in its use. Materials and Methods:The article is a comprehensive review of current literature, including clinical studies and trials involving testosterone therapy in women with low libido, especially in postmenopausal women. It highlights the various forms of testosterone supplementation, such as transdermal patches and topical gels, as well as monitoring recommendations for assessing testosterone levels and side effects during treatment. Results: Testosterone therapy has shown promising results in improving sexual desire, arousal, and satisfaction in women, particularly those postmenopausal or following surgical castration. While the therapy is generally well-tolerated, common side effects include acne, hirsutism, and voice deepening. The optimal dosing regimen and long-term safety, especially in premenopausal women, remain unclear, with ongoing studies indicating positive short-term outcomes. Clinical guidelines recommend individualized treatment. Conclusion:Testosterone replacement therapy is a viable option for women with HSDD, particularly in those with diminished testosterone levels due to menopause or surgical intervention. While promising, careful management is essential to mitigate side effects and ensure patient safety. Continued research is necessary to establish standardized treatment protocols and to further assess the long-term effects of testosterone therapy on women’s sexual health.